Placenta percreta - an audacious experience - Gadappa, Shrinivas; Deshpande, Sonali; Rajpurohit, Kalyani; Kalyankar, Bhakti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Maternal and fetal morbidity and mortality from placenta accreta are considerable and are associated with high demands on health resources. There is abnormally firm attachment of placenta to the uterine wall with the absence of deciduas basalis and incomplete development of Nitabuch’s layer. The reported incidence of placenta accreta has increased from approximately 0.8% in 1980s to 3 per 1000 in the last decade, occurring more frequently in future deliveries after caesarean section. Management of patients with a morbidly adherent placenta (placenta accreta, increta, or percreta) varies widely. Although the impact of a morbidly adherent placenta on pregnancy outcomes is well-described, no randomized trials have examined the management of pregnancies complicated by this disorder. As a result, recommendations for its management are based on case series and reports, personal experience, expert opinion, and good clinical judgement. We report a case of placenta percreta that was successfully managed by planned caesarean hysterectomy with prophylactic ligation of bilateral anterior division of internal iliac artery.